Aging: philosophers’ vision of oriental and occidental antiquity - Silvana Sidney Costa Santos (Rev Rene)
This bibliographical work objectived to approach the aging, leaving of the universal history philosophical reflections. In the Oriental civilization, Lao-Tsé correlated the age with the sanctity and Confúcio defended the filial pity. In the Occidental civilization, Socrates affirmed that the age didn’t to present any weight for the careful; Plato directioned the age to the peace and liberation and Aristotle affirmed that the elderly are not reliable. Cicero advised to find the pleasure in the age and Seneca defended the age as while the natural process. These philosophical reflections point for the necessary, difficult, pertinent and individual elaboration of the own aging of what work with the elderly.